Penerapan pemberdayaan masyarakat KUB penangkapan ikan melalui penggunaan Fish Finder di Kecamatan Sei Tualang Raso, Kota Tanjungbalai, Sumatera Utara - M. Harja Supena (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Sei Tualang Raso Subdistrict is one of the sub-districts in Tanjungbalai City, North Sumatra which has potential in the field of capture fisheries, which has 834 Capture Fisheries Households (RTP) which are incorporated into 3 Joint Business Groups (KUB) and have an average catch 2.100.4 kg/month with an income level of Rp. 28,460,000,-/month. The low level of income obtained is because the technology used is still traditional and has not used a fish finder. The purpose of this activity is to increase income and the role and function of the group as a forum for cooperation through the use of fish finder tools. The method used through the fishery extension program is in the form of group meetings, demonstrations of methods and conducting extension evaluations.